Fluoroscopic time: Necessary but not sufficient. Issue 3 (15th February 2015) - Balter, Stephen
Key Points Contrast utilization and fluoroscopic time decreased over time due to increased operator proficiency. There is no estimate of radiation hazard because radiation utilization was not recorded. Fluoroscopic time is an increasingly imprecise measure of radiation risk because of improving equipment configurations.